The Current Knowledge of the Role of PPAR in Hepatic Ischemia-Reperfusion Injury - M. Elias-Miró; M. B. Jiménez-Castro; M. Mendes-Braz; A. Casillas-Ramírez; C. Peralta (PPAR Research)
Strategies to improve the viability of steatotic livers could reduce the risk of dysfunction after surgery and increase the number of organs suitable for transplantation. Peroxisome proliferator-activated receptors (PPARs) are major regulators of lipid metabolism and inflammation. In this paper, we review the PPAR signaling pathways and present some of their lesser-known functions in liver regeneration. Potential therapies based on PPAR regulation will be discussed. The data suggest that further investigations are required to elucidate whether PPAR could be a potential therapeutic target in liver surgery and to determine the most effective therapies that selectively regulate PPAR with minor side effects.